2002
DOI: 10.1094/pdis.2002.86.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Blight and Dieback of Eucalyptus Species, Hybrids, and Clones in South Africa

Abstract: During 1998, a new disease appeared on trees representing a Eucalyptus grandis × E. nitens (GN) hybrid in a nursery in KwaZulu/Natal. The disease has subsequently spread to other Eucalyptus species, hybrids, and clones in nurseries and plantations throughout South Africa. Typical symptoms of the disease include dieback of young shoots and leaf blight. This ultimately leads to stunting of trees. The objective of this study was to isolate and identify the causal agent of the disease. A bacterium was consistently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
73
2
11

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 20 publications
2
73
2
11
Order By: Relevance
“…16S rRNA gene sequencing and multilocus sequence analyses (MLSA) revealed that the strains were phylogenetically closely related to Pantoea agglomerans, Pantoea stewartii and Pantoea ananatis. P. ananatis is the causal agent of bacterial blight and dieback of eucalyptus in South Africa (Coutinho et al, 2002). In 2001, Pantoea-like strains were isolated from eucalyptus trees exhibiting a similar disease in Uganda, Argentina and Uruguay and were thought to belong to P. ananatis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…16S rRNA gene sequencing and multilocus sequence analyses (MLSA) revealed that the strains were phylogenetically closely related to Pantoea agglomerans, Pantoea stewartii and Pantoea ananatis. P. ananatis is the causal agent of bacterial blight and dieback of eucalyptus in South Africa (Coutinho et al, 2002). In 2001, Pantoea-like strains were isolated from eucalyptus trees exhibiting a similar disease in Uganda, Argentina and Uruguay and were thought to belong to P. ananatis.…”
mentioning
confidence: 99%
“…Strains of Pantoea are diverse in their origin and geographical spread, and have been isolated from plants as well as from clinical samples. P. ananatis is the causal agent of bacterial blight and dieback of eucalyptus in South Africa (Coutinho et al, 2002). In 2001, Pantoea-like strains were isolated from eucalyptus trees exhibiting a similar disease in Uganda, Argentina and Uruguay and were thought to belong to P. ananatis.…”
mentioning
confidence: 99%
“…En Brasil, las especies bacterianas asociadas a manchas foliares incluyen a Erwinia psidii Rodrigues Neto, Robbs et Yamashiro, Pseudomonas cichorii (Swingle) Stapp, Rhizobiaceae, y Xanthomonas axonopodis Starr et Garces, , Gonçalves et al 2008, siendo X. axonopodis la especie predominante en Brasil (Gonçalves et al 2008). En Sudáfrica se asocia a Pantoea agglomerans (Beijerinck) Gavini et al y Pantoea ananatis (Serra-no) Mergaert et al con esta enfermedad (Coutinho et al 2002) al igual que en Uruguay (FAO 2006).…”
Section: Manchas Foliares Bacterianasunclassified
“…Con el tiempo las lesiones se fusionan, conduciendo a la caída prematura de las hojas provocando defoliación (Neves 2007, Gonçalves et al 2008, Alfenas et al 2009) (figura 1). En Sudáfrica y Uruguay se han descrito síntomas que incluyen hojas con aspecto reseco, concentrados principalmente sobre nervadura principal y pecíolo (Coutinho et al 2002). En Argentina y Paraguay, Ferreira et al (2001) describieron manchas bacterianas como lesiones angulares dispersas en todo el limbo, mayormente concentradas en los bordes de las hojas y próximo a la nervadura principal.…”
Section: Manchas Foliares Bacterianasunclassified
See 1 more Smart Citation